If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + 3) = (3x + 8) Reorder the terms: 2(3 + 2x) = (3x + 8) (3 * 2 + 2x * 2) = (3x + 8) (6 + 4x) = (3x + 8) Reorder the terms: 6 + 4x = (8 + 3x) Remove parenthesis around (8 + 3x) 6 + 4x = 8 + 3x Solving 6 + 4x = 8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + 4x + -3x = 8 + 3x + -3x Combine like terms: 4x + -3x = 1x 6 + 1x = 8 + 3x + -3x Combine like terms: 3x + -3x = 0 6 + 1x = 8 + 0 6 + 1x = 8 Add '-6' to each side of the equation. 6 + -6 + 1x = 8 + -6 Combine like terms: 6 + -6 = 0 0 + 1x = 8 + -6 1x = 8 + -6 Combine like terms: 8 + -6 = 2 1x = 2 Divide each side by '1'. x = 2 Simplifying x = 2
| j/5=1 | | 4x+3x-2x=2 | | 0.2*t^2+10.4=100 | | 6:3x=9 | | z=-36/12 | | a+(a+3)+(2a+b)=180 | | e=-120/-12 | | g=52/-4 | | f=-16/-4 | | 6a+4L=80 | | 36.18=.5(b+b)5.4 | | 36+(-28)+(-16)+24=y | | 7y-11y= | | x-3(2x-4x)=1+6x | | 5x-9=-7 | | 4(-5)(-6)=x | | 12(-5)=x | | -6(-5)(-6)=h | | -4(-6)(5)=x | | -19(-6)=y | | -8(-5)=x | | x^2+36+12x=0 | | -15(-5)=x | | 3(-6)=y | | (-3)(3)(-10)=t | | n=(16)(9)(-2) | | 3x^2+2xy+3y^2+2x=0 | | 1/2-5x=10 | | y=(20)(-5)(-5) | | 16t^2-12t-25=0 | | x+2:6=20 | | -15(10)=c |